A Study of Consumer Behaviour towards Genetically Modified Foods and the Moderating Effects of Health Consciousness. Issue 3 (September 2018) - Singhal, Neha
With growing environmentalism and health concerns, people have become more conscious of the types of food they consume and the way they are processed. The principle of the present research paper is to explore the behaviour of consumers towards genetically modified (GM) foods and the moderating role of health consciousness. The rationale behind the present study is to address the gap in the past research work wherein most of the researchers have emphasized on major factors that influence consumption of GM foods such as product acceptance, information, higher income and ethical consumption. Findings: This paper explores the effect of consumer's health consciousness on their GM food purchase. The key purpose of the study is to explore the influence of health consciousness of consumers in moderating consumer attitude towards their behaviour in context of GM food products. The results suggest that information provided by the government and the trusted regulatory help consumers to form positive attitude towards GM foods. Practical implications: The findings suggest that the marketer should revolve advertisement and marketing strategies around the issues pertaining consumer's health consciousness. Moreover, government and other trusted regulatory must ensure consumers that GM food are healthy and superior to conventional food. Originality/value: This is one of the primary studies to examine the moderating effect of a health consciousness that bears on GM foods. Its empirical findings are projected to benefit the sustained expansion of GM foods.